Influences of Interelectrode Distance and Innervation Zone on Electromyographic Signals - Smith, Cory M.; Housh, Terry J.; Zuniga, Jorge M.; Camic, Clayton L.; Bergstrom, Haley C.; Smith, Doug B.; Herda, Trent; Weir, Joseph P.; Hill, Ethan Cole; Jenkins, Nathaniel David Moyer; Schmidt, Richard J.; Johnson, Glen (International Journal of Sports Medicine, 2017)
The purpose of the present study was to examine the effects of electrode placements centered over and offset from the innervation zone (IZ) with different interelectrode distances (IED) on the time and frequency domain parameters of the electromyographic (EMG) signal during a fatiguing submaximal, isometric workout. 11 adults performed an isometric leg extension muscle action at 50% maximal voluntary isometric contraction (MVIC) to exhaustion. Electromyographic amplitude and frequency parameters were determined from electrode placements with different IED centered over, at proximal offset, at distal offset, and away from the IZ at 10, 50, and 100% of the time to exhaustion using an electrode array. There were greater absolute EMG amplitude and lower absolute EMG frequency for electrode placements over and offset from the IZ, but lower absolute EMG amplitude over than offset from the IZ regardless of IED at each time-point during the time to exhaustion. The absolute EMG frequency values were affected by the location relative to the IZ and IED of the electrode placements, and were greater for distal offset vs. proximal offset electrode placements at each time-point. Normalization of the EMG amplitude and EMG frequency values to MVIC eliminated differences due to IED and electrode placements during the fatiguing workout.
Keywords: EMG; fatigue; IZ; normalize; IED